Urinary Iodine levels in Residents of Azad Jammu and Kashmir - Samia Sarwar , Ifra Saeed , Zubia Razzaq (Journal of Rawalpindi Medical College, 2014)
Background: To evaluate the effectiveness of Universal Salt Iodization (USI) program in residents of Azad Jammu and Kashmir by measuring the Median Urinary Iodine (MUI) concentration. Methods: In this cross sectional study 100 healthy iodized salt users, for last two years, were included. All were euthyroid upon clinical and biochemical assessment. Serum and early morning urine samples were collected for the measurement of Thyroid Stimulating Hormone (TSH) and Median Urinary Iodine (MUI) concentration respectively. Serum and urine samples were stored at -20 C till analysis. TSH was measured by Chemiluminescent technique and Urinary iodine was determined by Modified Zak method. Results: Mean age of the subjects was 44±8 years. Study revealed that optimal level of urinary iodine was present in 82% of subjects. 1% of the subjects were severely deficient in their iodine nutrition while no one was found having MUI level more than adequate or excessive. Moderate and mild deficiency of iodine was recognized in 5% and 12% of the subjects respectively. Conclusion: Majority (82%) have optimal level of urinary iodine excretion. It reflects that the optimal level of salt iodization in the iodized salt is provided.Iodine excess was not recorded in any of the participants . Sustained efforts must be continued to monitor USI at the country level.